Carcass Traits, Mineral Retention, Blood Biochemistry and Economics of Broiler Chicken Fed Inorganic, Organic and Nano Zinc Supplemented Diets - Shubhnish; V.S. Panwar; B.S. Tewatia; Jyotsana (Indian Journal of Animal Nutrition, 2024)
The present study was planned to assess the effect of inorganic, organic and nano zinc supplemented diets on different carcass traits, haematological and serological parameters of broiler birds. One hundred and sixty one dayold broiler chicks were equally and randomly distributed into four treatment (T1, T2, T3 and T4) groups which were subdivided into four replicates having ten birds in each. Birds were reared on deep litter system up to 6 weeks of age. T1 group was kept as control and offered maize-soybean meal based diet without any source of zinc in mineral mixture. Treatment groups T2, T3 and T4 were supplemented with inorganic, organic and nano zinc, respectively.The carcass characteristics data revealed that dressed weight and the weight of liver, gizzard and kidney significantly increased(P